Identifying Stakeholders’ Needs for Agricultural Communications in Higher Education Curriculum in Australia - Landee Thorn; Courtney Meyers; Steve Fraze; Cindy Akers (Journal of Applied Communications, 2023)
Agriculture is a vital part of the Australian economy. With an industry poised for growth, and a growing disconnect between consumers and agriculture, additional communication efforts are needed. The purpose of this study was to complete a curriculum visioning process to inform agricultural communications curriculum development in Australia. This study used a qualitative research design consisting of face-to-face, semi-structured interviews with individuals from 14 agricultural organizations and two universities. The results indicated the industry is addressing many challenges, but also has opportunities that would benefit from strategic communication efforts. Participants provided suggestions regarding the specific communication skills and agriculture knowledge future employees should possess. Recognizing these competencies informed the curriculum visioning process for agricultural communications as an academic discipline within Australian higher education. Recommendations for both practice and future research are provided.
Keywords: curriculum development; academic programs; teaching; Australia